2015
DOI: 10.1002/anie.201411973
|View full text |Cite
|
Sign up to set email alerts
|

Developing Conjugated Polymers with High Electron Affinity by Replacing a CC Unit with a BN Unit

Abstract: The key parameters of conjugated polymers are lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy levels. Few approaches can simultaneously lower LUMO and HOMO energy levels of conjugated polymers to a large extent (>0.5 eV). Disclosed herein is a novel strategy to decrease both LUMO and HOMO energy levels of conjugated polymers by about 0.6 eV through replacement of a C-C unit by a B←N unit. The replacement makes the resulting polymer transform from an electron dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 217 publications
(147 citation statements)
references
References 63 publications
2
141
0
3
Order By: Relevance
“…More recently,He et al described the Suzuki-Miyaura and Stille copolymerization of B À Np henanthrene derivatives that are derived from ring-expansion of 9-borafluorenes with aromatic azides. [181] Theo rganoboron component may be viewed as an analog of cyclopentadithiophene, ac ommon building block in organic electronics,b ut placement of the B-N unit lowers both the HOMO and LUMO energy levels,t hus dramatically enhancing the acceptor character.T he borane functionalization of N-heterocyclic polymers can also be achieved in ap ost-polymerization modification as demonstrated by Ingleson, Tu rner et al [182] They used the Lewis base directed electrophilic borylation of 107 to generate homopolymer 108 and related partially borylated copolymers (Scheme 12 b). [180] Using aC ÀNc helated borane monomer,L iu et al developed tetracoordinate borane polymers as new acceptor materials for OSC applications.T hey demonstrated that the combination of borane-complexed thienylthiazolyl units with organic electron-acceptors results in n-type materials that are highly effective in all-polymer solar cells giving PCEs as high as 5% (106,S cheme 12 a).…”
Section: Other Polymers Containing Conjugated Heterocyclesmentioning
confidence: 99%
“…More recently,He et al described the Suzuki-Miyaura and Stille copolymerization of B À Np henanthrene derivatives that are derived from ring-expansion of 9-borafluorenes with aromatic azides. [181] Theo rganoboron component may be viewed as an analog of cyclopentadithiophene, ac ommon building block in organic electronics,b ut placement of the B-N unit lowers both the HOMO and LUMO energy levels,t hus dramatically enhancing the acceptor character.T he borane functionalization of N-heterocyclic polymers can also be achieved in ap ost-polymerization modification as demonstrated by Ingleson, Tu rner et al [182] They used the Lewis base directed electrophilic borylation of 107 to generate homopolymer 108 and related partially borylated copolymers (Scheme 12 b). [180] Using aC ÀNc helated borane monomer,L iu et al developed tetracoordinate borane polymers as new acceptor materials for OSC applications.T hey demonstrated that the combination of borane-complexed thienylthiazolyl units with organic electron-acceptors results in n-type materials that are highly effective in all-polymer solar cells giving PCEs as high as 5% (106,S cheme 12 a).…”
Section: Other Polymers Containing Conjugated Heterocyclesmentioning
confidence: 99%
“…[179] Die Fluorid-bindenden Eigenschaften der resultierenden Polymere 104 (Abbildung 28, unten links) wurden untersucht und zeigten eine schaltbare Lumineszenzantwort. [181] Die Organobor-Komponente kann als Analogon von Cyclopentadithiophen, einem gängigen Baustein in der organischen Elektronik, be-trachtet werden, aber die Platzierung der B-N-Einheit senkt sowohl die HOMO-als auch die LUMO-Energiewerte und verbessert damit den Akzeptorcharakter drastisch. [180] Unter Verwendung eines C-N-chelatisierten Boran-Monomers entwickelten Liu et al Boran-Polymere mit vierfachkoordinierten Bor-Zentren als neue Akzeptormaterialien für Anwendungen in OSCs.S ie zeigten, dass die Kombination von Bor-komplexierten Thienylthiazolyl-Einheiten mit organischen Elektronenakzeptoren zu n-Typ-Materialien führt, die in All-Polymer-Solarzellen sehr effektiv sind und PCEs bis zu 5% erreichen (106;S chema 12 a).…”
Section: Angewandte Chemieunclassified
“…4,5 As normal homopolymers, e.g. 11 In this manuscript, we report the application of B←N unit to tune the LUMO/HOMO levels of polymer donor materials for enhanced PSC device performance. A large family of D-A type polymer donors with finely tuned LUMO/HOMO levels have been reported to exhibit excellent PSC device performance.…”
Section: Introductionmentioning
confidence: 99%